Efektivitas Flipped Classroom berbasis Inkuiri Terbimbing sebagai Sistem Pembelajaran pada Materi Larutan Asam Basa kelas XI SMA - Kurnia Lenggogeni; Mawardi Mawardi (Postgraduate, University of Mataram, 2022)
This study aims to determine the effectiveness of flipped classroom based on guided inquiry learning system on acid-base solutions toward students learning outcomes of XI class senior high school students that had been tested valid and practical. This type of research is quasi-experimental with a Non-Equivalent Control Group Design. The sample class used was XI Mipa 1 as a control class and XI Mipa 2 as an experimental class, with the total of students were 69 using the purposive sampling technique. The instrument used in this study was a multiple choices question to assess students learning outcomes in the cognitive domain. The result of this study to obtain the N-gain value from the experimental class and control class with the values are 0.80 and 0.73, respectively, which indicates the value of experimental class is higher than control class. Furthermore, for the t-test, the value is 3.18, and the t-table value is 1.99. It concludes that using flipped classroom based on guided inquiry learning system on acid-base solutions improve students learning outcomes effectively